ظاهرة الاستقطاب في تراكيب معدن - عازل – نصف ناقل (Latakia University Journal -Basic Sciences Series, 2014)
يعدّ هذا البحث دراسة نظرية لآلية تشتت حاملات الشحنة في قنوات ناقلة لجملة مؤلفة من تركيب(MIS)(معدن – عازل – نصف ناقل ). عندما يكون العازل مستقطباً، فإن  للناقلية في المستوى السطحي لنصف الناقل سلوكاً استقطابياً نتيجة انتقال الشحنات عبر الحدود الفاصلة. ويهدف هذا العمل إلىدراسة تأثير الكمون الذاتي لحاملة الشحنة(إلكترون أو ثقب)، وكمون الاستقطاب على طاقة الحالة الأساسي لبولارون الإلكترون في طبقة نصف الناقل. من خلال حل معادلة شرودينغر، ومناقشة بعض الحالات الخاصة للحل، مثل الحالة التي يكون فيها للكمون الشكل المثلثي(حالة تماس معدن-نصف ناقل).This research is a theoretical study for the scattering mechanism of the charge carrier in the transport tunnels of system consisting of metal-insulator- semiconductor (MIS)- When the insulator is polarized where the conductivity of surface for semiconductor polarization behavior due to charge transfer during interfaces. The aim of this research is to investigate the effect of self-action and polarization potentials on the ground state of electron- polaron in semiconductor layer by means of is olating the Schrodinger equation and discussion of some special cases such as the potential is triangular form (case of contact metal – semiconductor).